Bio-Monitoring Study on Tropospheric Ozone Using White Clover at Bangladesh Agricultural University Farming Area - Islam, MT; Ashraf, MA; Sattar, MA (Progressive Agriculture, 2014)
A pot experiment was conducted at the field laboratory of the Dept. of Environmental Science, Bangladesh Agricultural University, Mymensingh to asses the visual ozone injury in white clover crops (Trifolium repens cv. Regal) started from May 13, 2007. Two genotypes of white clover were used of which one was ozone susceptible (NC-S) and the other was ozone resistant (NC-R). Each genotype was replicated into 20. The data on total plant dry matter harvested thrice at 28 days interval resulted in increasing biomass gradually in later harvests. The Monthly mean ozone values collected from passive ozone sampler during April to August07 was recorded as 29, 35, 49, 28, and 61 ppb respectively, which seemed that ozone concentrations in the troposphere is increasing gradually in Bangladesh. The susceptible NC-S showed visual ozone injury symptom from very slightly (0-1%) to slight (1-5%) where as the resistant cultivar showed no visual injury symptom. The ozone susceptible cultivar generally produced comparatively less biomass than the resistant one at every harvest. DOI: http://dx.doi.org/10.3329/pa.v18i2.18243 Progress. Agric. 18(2): 215 - 222, 2007